Isolation and phenotypic characterization of tumor cells of patients with a diagnosis of ovarian cancer. Issue 4 (24th September 2019) - Gutiérrez‐Castañeda, Luz D.; Tovar‐Parra, David; Quintero, Gloria; Amezquita, Lorena; Guerrero, Carlos; Sanabria, Daniel
Abstract: Ovarian cancer is the fifth leading cause of cancer‐related deaths. It causes approximately 125, 000 deaths per year worldwide; its diagnosis is made in advanced stages resulting in a high mortality rate. The objective of the study was optimizing the isolation of cells obtained from the solid tumor and ascitic fluid of patients with ovarian cancer and the phenotype with markers related to the epithelial–mesenchymal transition. For this, the solid tumor tissue was disaggregated and cultivated with different methodologies. As a result, cell growth was obtained and epi‐immunofluorescence was performed using antibodies against E‐cadherin, EpCAM, N‐cadherin, vimentin, CD133, and CD44. The primary culture from the solid tumor was obtained using Dispase II and DMEM/F12. Finally, heterogeneity was detected in terms of the expression of mesenchymal and epithelial type markers in the two types of isolated cells. Additionally, CD133 and CD44 expression was detected, proteins associated with the tumor stem cells phenotype. Abstract : The ovarian cancer cells isolated were heterogeneous. This was detected in terms of expression of mesenchymal and epithelial type markers. Additionally, CD133 and CD44 expression was detected, proteins associated with the tumor stem cells phenotype.